IKTINAAZ AN-NUQUUD - AHKAAMUHU WA AATSAARUHU WA SUBUL MU'ALAJATIHI ( Dirasah Muqaranah bi al-Iqtishad al-Islamy) - Muhammad Roshdi Ibrahim Mas'ud (IAIN Bone, 2020)
Wealth is one of the greatest blessings that God has bestowed on man, with which the connection between peoples has increased, and many things have been accomplished, for it is truly the engine of the economy, has increased its speed, and has reduced a lot of time in matters that were done through trade-offs. People must not deviate from the money from what it was created for, and take it as a tool of hoarding, as this is contrary to its purpose, but given that some people may deviate from grace, then take the criticism as a destination after it was a means, which results in a lot of harm, so the ruling of the street comes in a way that violates everything that contradicts Therefore, preventing Islam from Iktinaz (hoarding wealth by not paying zakat on it) is not just an occasional phenomenon in Islamic law, but rather it expresses one of the serious differences between Islamic doctrine and capitalist doctrine, and reflects the way in which Islam was able to get rid of the problems of capitalism, resulting from the poor capitalist role of using criticism, which It leads to the most dangerous complications, threatens the movement of production and constantly rocks capitalist society.